OC-070 Dietary Supplementation With Fodmaps Increases Fasting Colonic Volume And Breath Hydrogen In Healthy Volunteers: A Mechanistic Study Using Mri. (9th June 2014) - Major, G; Teale, A; Pritchard, S; Marciani, L; Whelan, K; Gowland, P; Spiller, R
Abstract : Introduction: Indigestible fermentable carbohydrates, grouped as FODMAPs, have been proposed to induce gastrointestinal symptoms. Some, such as oligofructose (OF), are prebiotics and modify the microbiota. The metabolic activity of the microbiota affected transit time in a mouse model. 1 This study hypothesised that dietary supplementation with OF would shorten whole gut transit time (WGTT) and improve the capacity of the microbiota to metabolise a FODMAP challenge. Methods: The study was an open-label case series. 16 healthy volunteers underwent fasting MRI to assess colonic volume [2] and the position of 5 transit markers ingested 24 h earlier from which WGTT could be calculated. 3 Breath hydrogen (H2 ) and methane (CH4 ) were also measured. Subjects then consumed an inulin challenge drink (ICD): 500 ml water containing 40 g inulin. Inulin is fermented in the colon and known to increase H2 and colonic volume. 4 After ICD subjects could sip water and were given a low FODMAP lunch but no other food was allowed. 8 h post-ICD MRI was repeated. Breath measurements were repeated 4 and 8 h post-ICD. Subjects then supplemented their usual diet with OF (gift from BENEO, Germany), 5 g twice daily, for a week. Fasting and post-ICD measurements were then repeated. Dietary questionnaires were completed for the weeks preceding MRIs to assess dietary fructan intake. Results: Median [IQR] given unless stated as mean [95% CI]. Fasting colonic volumes (510 ml [400–710]) increased by mean 94 ml [12 – 177, p = 0.03] after OF. Fasting H2 (33 ppm [9–87]) increased by mean 39 ppm [6 – 71, p = 0.02]. WGTT (34 h [10 – 45]) increased by 19 h [-9 – 42] but this increase did not reach significance (p = 0.09, Wilcoxon). Colonic volumes post-ICD were similar across weeks (mean 726 ml [667–785]). The change from baseline was significant in week 1 but not week 2 due to the difference in fasting volumes. There was no difference between weeks 1 and 2 in H2 at 4 or 8 h after ICD. CH4 did not change. Dietary fructan intake was similar in both weeks (mean < 8 g/ day). Conclusion: OF increased fasting colonic volumes by 18%. H2 also rose. This may reflect increased bacterial mass with increased capacity for fermentation. The suggestion that OF slows WGTT is surprising and warrants further investigation. MRI can complement research on the microbiota to describe its impact on gut physiology. References: 1 Kashyap P et al. Gastroenterology 2013;144(5):967–77 2 Chaddock G et al . Neurogastroenterology and Motility 2013 3 Pritchard S et al . Neurogastroenterol Motil 2013 4 Murray K et al . Am J Gastroenterol 2013 Disclosure of Interest: None Declared.